Involving users in the delivery and evaluation of mental health services: systematic review - Simpson, Emma L (BMJ, 2002)
OBJECTIVES: To identify evidence from comparative studies on the effects of involving users in the delivery and evaluation of mental health services. DATA SOURCES: English language articles published between January 1966 and October 2001 found by searching electronic databases. STUDY SELECTION: Systematic review of randomised controlled trials and other comparative studies of involving users in the delivery or evaluation of mental health services. DATA EXTRACTION: Patterns of delivery of services by employees who use or who used to use the service and professional employees and the effects on trainees, research, or clients of mental health services. RESULTS: Five randomised controlled trials and seven other comparative studies were identified. Half of the studies considered involving users in managing cases. Involving users as employees of mental health services led to clients having greater satisfaction with personal circumstances and less hospitalisation. Providers of services who had been trained by users had more positive attitudes toward users. Clients reported being less satisfied with services when interviewed by users. CONCLUSIONS: Users can be involved as employees, trainers, or researchers without detrimental effect. Involving users with severe mental disorders in the delivery and evaluation of services is feasible.